Assessment of Endothelial Dysfunction in Acute and Convalescent Phases of Kawasaki Disease Using Automated Edge Detection Software: A Preliminary Study From North India. Issue 4 (June 2021) - Routhu, Santhosh Kumar; Singhal, Manphool; Jindal, Ankur Kumar; Kumar, Vivek; Yadav, Ashok Kumar; Singh, Surjit
Abstract : Objective: The aim of this study was to assess endothelial dysfunction in acute and convalescent phases of Kawasaki disease (KD) using automated edge detection software. Methods: This was a case-control study to assess the flow-mediated dilatation (FMD) of brachial artery (BA) in patients with KD during acute phase and at least 3 months after diagnosis. A 10-MHz multifrequency linear array probe attached to a high-resolution ultrasound machine (PHILIPS Medical System-IU22) was used to acquire the images. Automated edge detection software was used to assess BA diameter. Results: A total of 16 children with KD and 16 healthy children were enrolled in the study. Mean ± SD maximum BA diameter was found to be significantly low during the acute stage of KD (2.56 ± 0.36 mm) as compared with the convalescence phase (2.93 mm ± 0.31) and in healthy controls (2.95 mm ± 0.56). The mean ± SD percentage change in the FMD was found to be significantly low in the acute phase of KD (12.32 ± 6.2) as compared with the convalescence phase of KD (17.99 ± 8.13) and healthy controls (26.88 ± 12.76). The mean ± SD percentage change in the FMD was also found to be significantly low in the convalescence phase of KD as compared with healthy controls. Conclusions: The FMD of the BA is significantly reduced in patients during the acute and convalescence phase of KD as compared with normal healthy children. The endothelial dysfunction was present even in patients who had no obvious coronary artery abnormalities during the acute stage.